2010
DOI: 10.1016/j.jcmg.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy: A Unique Cardiomyopathy With Variable Ventricular Morphology

Abstract: Takotsubo cardiomyopathy is an important differential diagnosis of acute coronary syndrome. It is characterized by normal (or near-normal) coronary arteries, regional wall motion abnormalities that extend beyond a single coronary vascular bed, and often, a precipitating stressor. Variants of the classical left ventricular apical ballooning, including mid- or basal left ventricular wall motion abnormalities, are increasingly recognized. Takotsubo cardiomyopathy is not rare, and heightened awareness of this uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
188
1
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(217 citation statements)
references
References 76 publications
3
188
1
12
Order By: Relevance
“…Takotsubo cardiomyopathy is characterized by apical ballooning with normal or increased contractility of the base of the left ventricle and is triggered by severe emotional stress (1)(2)(3). Although the physiological findings mimic acute myocardial infarction, the etiology of Takotsubo cardiomyopathy does not involve coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…Takotsubo cardiomyopathy is characterized by apical ballooning with normal or increased contractility of the base of the left ventricle and is triggered by severe emotional stress (1)(2)(3). Although the physiological findings mimic acute myocardial infarction, the etiology of Takotsubo cardiomyopathy does not involve coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is characterized by transient systolic and diastolic left ventricular dysfunction with a variety of wall-motion abnormalities. 2,3 It predominantly affects elderly women and is often preceded by an emotional or physical trigger, 4 but the condition has also been reported with no evident trigger. In the acute phase, the clinical presentation, electrocardiographic findings, and biomarker profiles are often similar to those of an acute coronary syndrome.…”
mentioning
confidence: 99%
“…All large-cohort reports of TTC have shown that most patients presenting with the syndrome are postmenopausal women (5). However, it has also been reported in men and patients <50 years (1,3,15,16) and even in a 2-year-old girl (22). In the first large Japanese series describing TTC, 76 patients were women, 12 were men, and the median age was 67 ± 13 years (2).…”
Section: The Patientmentioning
confidence: 88%
“…It is an important differential in diagnosis of acute coronary syndrome (ACS) due to its similar presentation. However, it distinguishes itself from an ACS in the fact that regional wall motion abnormalities extend beyond a single coronary vascular bed and are reversible, and epicardial coronary occlusion is absent (1). In TTC, left ventricular (LV) dysfunction can be remarkably depressed but recovers within a few weeks (2) in the vast majority of patients.…”
Section: Introductionmentioning
confidence: 99%